THE GOTHIC NOVEL: ORIGINS AND INFLUENCE ON ENGLISH LITERATURE (Ustozlar uchun, 2025)
This article examines the origins, development, and lasting influence of the Gothic novel in English literature. Emerging in the late eighteenth century, the Gothic genre combined elements of medievalism, mystery, terror, and the supernatural. The study explores key works and authors, including Horace Walpole, Ann Radcliffe, Matthew Lewis, Mary Shelley, and Bram Stoker, and analyzes how Gothic themes evolved from early romanticism to Victorian sensationalism and modern horror fiction. The article argues that the Gothic novel not only shaped literary movements but also influenced cultural perceptions of fear, identity, and the unknown.